2011
DOI: 10.1179/105307811805472710
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Psychological Theory of Mental Illness, Supported by Research in Saudi Arabia

Abstract: This article proposes a theory of psychological disturbance (mental illness) as a cultural phenomenon. The theory is based on -and extends --the general cultural psychological theory of Vygotsky, Luria, and Leontiev, as well as the specific social approach to psychopathy of Fromm, Foucault, Laing, and Rieber. We demonstrate that the psychodynamics of individual disturbances are shaped by normative, macro cultural factors, such as gender norms, religious doctrine, family structure, architecture, and clothing. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…This pattern of sex-biased perception of parents has been observed in a sample of college students in the United States and Canada (Salmon et al, 2012), as well as in a sample of children and adults seen in a counseling clinic in the United States (Kiracofe & Kiracofe, 1990) and are in agreement with the findings of Ratner and El-Badwi (2011), who reported that Saudi boys perceived their mother as more compassionate than their father.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This pattern of sex-biased perception of parents has been observed in a sample of college students in the United States and Canada (Salmon et al, 2012), as well as in a sample of children and adults seen in a counseling clinic in the United States (Kiracofe & Kiracofe, 1990) and are in agreement with the findings of Ratner and El-Badwi (2011), who reported that Saudi boys perceived their mother as more compassionate than their father.…”
Section: Discussionsupporting
confidence: 77%
“…Ahmed et al (2010) reported that males in Saudi Arabia and Egypt perceived their mothers as being less accepting of sons than of daughters and felt they were closer to their fathers than to their mothers (Al-Rowais, Al-Faris, Mohammad, Al-Rukban, & Abdulghani, 2010). Findings in other studies with Arab populations (Sayid, 2000;Zaidan, 1990) do not support this observation; for example, Ratner and El-Badwi (2011) found that Saudi males believed that their mothers were more receptive and caring than their fathers.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…If a family escort (mehrum) is present (i.e., father, mother, husband, sibling), a woman may meet with a male psychiatrist, psychologist, psychiatric social worker or counselor, although there may be no physical contact including hand-shaking. The expressions of mental illness are heavily influenced by every one of these religious and cultural factors, and approaches to mental health care must take them into account [85].…”
Section: Cultural and Religious Influencesmentioning
confidence: 99%